First generation of multifunctional peptides derived from latarcin-3a from Lachesana tarabaevi spider toxin - de Moraes, Luiz Filipe Ramalho Nunes; Silva, Patrícia Souza e; Pereira, Tábata Camila Pereira Leite; Almeida Rodrigues, Thiago Antônio; Farias Frihling, Breno Emanuel; da Costa, Rosiane Andrade; Torquato, Heron Fernandes Vieira; Lima, Cauê Santos; Paredes-Gamero, Edgar Julian; Migliolo, Ludovico (Frontiers in Microbiology, 2022)
The need for discovering new compounds that can act selectively on pathogens is becoming increasingly evident, given the number of deaths worldwide due to bacterial infections or tumor cells. New multifunctional biotechnological tools are being sought, including compounds present in spider venoms, which have high biotechnological potential. The present work aims to perform the rational design and functional evaluation of synthetic peptides derived from Lachesana tarabaevi spider toxin, known as latarcin-3a. The antimicrobial activity was tested against Gram-positive and -negative bacteria, with minimum inhibitory concentrations (MIC) between 4 to 128 µg.mL-1. Anti-biofilm tests were then performed to obtain MICs, where the peptides demonstrated activity from 4 to 128 µg.mL-1. In vitro cell cytotoxicity assays were carried out from tumor cell lines, lineages C1498, Kasumi-1, K-562, Jurkat, MOLT4 and Raji. Erythrocyte integrity was evaluated in the presence of synthetic peptides analogue, which did not promote hemolysis at 128 µg.mL-1. The peptide that showed the best antibacterial activity was Lt-MAP3 and the best antitumor was Lt-MAP2. In conclusion, rational design of multifunctional antimicrobial peptides may be promising alternative tools in the treatment of emerging diseases such as bacterial infections and tumor cells.